Teaching communication skills to OTL-HNS residents: multisource feedback and simulated scenarios - Pier-Luc Beaudoin; Mathilde Labbé; Amanda Fanous; Meredith Young; Jamie Rappaport; Yoon Soo Park; John Manoukian; Lily H. P. Nguyen (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Effective communication has been linked to a reduction in adverse events and improved patient compliance. Currently in Otolaryngology – Head and Neck Surgery (OTL-HNS) residency programs, there is limited explicit teaching of communication skills. Our objective was to implement an educational program on communication skills for residents using multisource assessment in several simulation-based contexts throughout residency. Methods For three consecutive years, OTL-HNS residents were recruited to participate in a total of nine simulation-based clinical scenarios in which communication skills could be honed. This educational program was designed to provide instruction and practice of challenging ethics scenarios, with communication efficacy as a secondary goal. To facilitate this goal, a multisource assessment was paired with a debriefing process that involved attending staff, observing and participating residents, standardized patients, and invited content experts. Results Seventeen residents completed the curriculum for at least two consecutive years from 2009 to 2011. The internal-consistency reliability of the scenarios ranged from 0.88 to 0.96. The intraclass correlation was 0.19, as expected in this context. There was no statistical difference in the mean ratings of performance across post-graduate year (PGY) level (p = 0.201). Results from the random-intercept regression indicated that, on average, a learner’s mean rating at baseline was 3.6/5 and increased significantly by 0.25 points per year (p < 0.05) as assessed by OTL-HNS staff members and peers. No significant improvement across time was found for ratings by non-medical assessors. Conclusion Implementing an educational program focused on communication skills using a multisource assessment in various contexts has shown to be potentially effective at our institution, and resulted for yearly improvement and consolidation of performance of OTL-HNS residents as judged by faculty and residents. The inclusion of a multisource assessment in the simulation curriculum is key to allow for the representation of different perspectives on communication skills, for both the assessment and the debriefing process. Future studies are needed to explore the possibility of fully integrating this educational program into residence training in order to support deliberate communication skills teaching.